Meningkatkan Aktivitas, Motivasi dan Hasil Belajar Matematika Menggunakan Model Piring Antik Pada Siswa Sekolah Dasar - M. Irham; Ratna Purwanti (CV. ITTC INDONESIA, 2023)
This study aims to describe how teacher activities and student activities as well as analyze the increase in motivation and student learning outcomes in class V SDN Sidorejo 1 Barito Kuala Regency by using a model, namely PIRING ANTIK which is a combination of Problem Based Learning (PBL) models, Mathematics Learning Realistic (PMR) and Snowball Throwing. The type of research used was Classroom Action Research (CAR), which was carried out in three meetings. The research subjects were fifth grade students at SDN Sidorejo 1, totaling 20 students, consisting of 12 male students and 8 female students. The data in this study were obtained from observations and written tests. Then the conclusion from the final results of this study is that teacher activity in this study has increased by obtaining results on very good criteria. Student activity has increased with the final result obtaining very active criteria. Student motivation has increased with the final result obtaining very high criteria. And student learning outcomes individually obtain or exceed the KKM that has been set, namely ≥75 and classical learning outcomes, namely ≥80% of students in the class obtain a final score that meets the specified completeness criteria, namely ≥75.